Fermentation Processes 2017
DOI: 10.5772/64640
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation and Redox Potential

Abstract: Redox potential, known as oxidation-reduction or oxidoreduction potential (ORP), not only indicates the reduction and oxidation capacity of the environment but also reflects the metabolic activity of microorganisms. Redox potential can be monitored online and controlled in time for more efficient fermentation operation. This chapter reviews the enzymes that modulate intracellular redox potential, the genetically engineered strains that harbor specific redox potential-regulated genes, the approaches that were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…In darkness, stored starch is converted to pyruvate and ethanol is produced from pyruvate catalyzed by pyruvate decarboxylase and alcohol dehydrogenase. Under the prevalent dark, anaerobic conditions, fermentation pathways are upregulated to allow the cell to generate reductants for carrying basal cellular activity in the absence of repressed photosynthetic machinery …”
Section: Resultsmentioning
confidence: 99%
“…In darkness, stored starch is converted to pyruvate and ethanol is produced from pyruvate catalyzed by pyruvate decarboxylase and alcohol dehydrogenase. Under the prevalent dark, anaerobic conditions, fermentation pathways are upregulated to allow the cell to generate reductants for carrying basal cellular activity in the absence of repressed photosynthetic machinery …”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of these classes of compounds prepares the yeasts for successive rounds of division and helps to fortify the plasma membrane against proton stress and the dehydrating effects of alcohol [ 49 ]. Actively dividing yeast also decreases the redox potential by excreting reductive compounds (e.g., glutathione, protons) [ 21 ]. Previous work has shown that as a yeast population reaches an “ORP Minimum”, the biological and extracellular chemical production of H 2 S spikes, causing the yeast population to undergo a physiological transition from exponential growth phase into stationary phase [ 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated the effectiveness of using ORP as a strategy for controlling the activity of biological systems [ 15 ]. In low-oxygen yeast fermentations, changes in redox potential are primarily driven by the physiological and metabolic status of the yeast population: as yeast depletes molecular O 2 , produces CO 2 , and excretes reductive metabolites, it causes the ORP to decrease [ 21 ]. As fermentation progresses, an “ORP minimum” is reached, which corresponds with an increase in hydrogen sulfide (H 2 S) due to yeast amino acid metabolism and spontaneous extracellular reduction of elemental sulfur at low redox potential [ 18 , 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although many fermentation processes have been well developed with long-term operability, cost saving is an endless effort, particularly for biofuels and bio-based chemicals production at bulk quantity such as ethanol and butanol to address global concern on sustainable development (Kracke et al 2018). Since redox reactions and homeostasis are basis for intracellular metabolism, ORP status controls metabolites profiles, which subsequently offers a strategy to direct the pathway for efficient production of more and more materials and energy (Liu et al 2017a). With advanced technologies that can detect ORP levels and its intracellular influence on gene expression, protein biosynthesis and metabolites caused by ORP shifts, mechanism underlying this phenomenon can be elucidated.…”
Section: Redox Potentialmentioning
confidence: 99%
“…More robust strains and optimized processes can be developed by redox potential which can be controlled by metabolic modifications and bioprocess engineering levels, which have been highlighted in ethanol and butanol fermentations under microaerobic and anaerobic conditions (Liu et al 2017a). Figure 3 shows the standard ORP of some redox pairs in an intracellular metabolism and it is affected by temperature, aerobic or anaerobic conditions.…”
Section: Redox Potentialmentioning
confidence: 99%